The Institutional Agency of Football Club (FC) Barcelona in Catalonia’s Protodiplomatic Strategy Toward Spain (2019–2021) - Nsw, Rayia Khaza; Laode Muhamad Fathun (Journal of Paradiplomacy and City Networks, 2026)
This article examines FC Barcelona’s institutional agency in Catalonia’s protodiplomacy strategy toward Spain following the 2017 independence referendum, with a specific focus on the period 2019–2021. Catalonia, as an autonomous region with a strong cultural and political identity, saw an escalation of protodiplomatic efforts following the curtailment of its autonomy by the Spanish Constitutional Court in 2010. Within this dynamic, FC Barcelona emerged as a significant non-state actor in projecting Catalan identity onto the global stage. This study aims to identify and analyze the strategic role played by the club in supporting regional protodiplomatic narratives and agendas. Using a descriptive qualitative method grounded in document analysis and interviews, this study draws upon Clive Archer’s role theory, the concept of protodiplomacy by Kuznetsov and Soldatos, and Benedict Anderson’s idea of imagined communities. The findings indicate that FC Barcelona consistently exercises its institutional agency through the promotion of identity elements such as language, flag symbols, and Catalan historical narratives. Despite facing sports regulatory restrictions and political pressure from the Spanish central government, the club effectively represents the Catalan identity struggle. In conclusion, FC Barcelona functions as a strategic instrument in Catalan protodiplomacy, affirming its role that transcends that of a commercial sports entity to become an influential political representation of identity on the international stage.